Survival strategies in arctic ungulates - Tyler, N. J. C.; Blix, A. S. (Rangifer, 1990)
Arctic ungulates usually neither freeze nor starve to death despite the rigours of winter. Physiological adaptations enable them to survive and reproduce despite long periods of intense cold and potential undernutrition. Heat conservation is achieved by excellent insulation combined with nasal heat exchange. Seasonal variation in fasting metabolic rate has been reported in several temperate and sub-arctic species of ungulates and seems to occur in muskoxen. Surprisingly, there is no evidence for this in reindeer. Both reindeer and caribou normally maintain low levels of locomotor activity in winter. Light foot loads are important for reducing energy expenditure while walking over snow. The significance and control of selective cooling of the brain during hard exercise (e.g. escape from predators) is discussed. Like other cervids, reindeer and caribou display a pronounced seasonal cycle of appetite and growth which seems to have an intrinsic basis. This has two consequences. First, the animals evidently survive perfectly well despite enduring negative energy balance for long periods. Second, loss of weight in winter is not necessarily evidence of undernutrition. The main role of fat reserves, especially in males, may be to enhance reproductive success. The principal role of fat reserves in winter appears to be to provide a supplement to, rather than a substitute for, poor quality winter forage. Fat also provides an insurance against death during periods of acute starvation.